Assessing campus sustainability literacy and culture: How are universities doing it and to what end? - Lad, Nikita; Akerlof, KL (Frontiers in Sustainability, 2022)
Institutions of higher education have increasingly focused on data-driven decision-making and assessments of their sustainability goals. Yet, there is no agreement on what constitutes sustainability literacy and culture (SLAC) at colleges and universities, even though promoting these types of campus population-level changes is often seen as key to the greening of higher education. It remains unclear what motivates institutions to measure these constructs, the barriers they face in doing so, and how they use these assessments to improve sustainability outcomes. In order to understand how universities are conducting SLAC assessments and for what purpose, we carried out an analysis of a subgroup of institutions ̶ doctoral universities with very high research activity (R1) ̶ with respect to institutional organizational learning (OL). Semi-structured interviews were conducted with administrators of 20 R1 universities that reported SLAC assessments (2017-2020) in the Association for the Advancement of Sustainability in Higher Education’s STARS rating system. As anticipated, R1 universities reported conducting SLAC assessments for STARS points, but they also are motivated by the potential for the data to inform campus programs. Challenges in conducting assessments included: lack of institutional prioritization, difficulty conducting the surveys, inadequate resources, institutional barriers, and perceived methodological inadequacies. While very few of the higher OL institutions pointed to lack of institutional prioritization as a problem, more than half of lower OL universities did. Institutional support, having a dedicated office, and using survey incentives served as facilitators. This is one of the first studies to relate higher education OL to sustainability assessments. OL is likely to be an important construct in furthering an understanding of the institutional capacities required for implementation of assessments and their effectiveness in evidence-based decision-making.